Rolipram Improves Outcome in a Rat Model of Infant Sepsis-Induced Cardiorenal Syndrome - Sims, Clark R.; Singh, Sharda P.; Mu, Shengyu; Gokden, Neriman; Zakaria, Dala; Nguyen, Trung C.; Mayeux, Philip R. (Frontiers in Pharmacology, 2017)
While the mortality rate associated with sepsis in children has fallen over the years, it still remains unacceptably high. The development of both acute cardiac dysfunction and acute kidney injury during severe sepsis is categorized as type 5 cardiorenal syndrome (CRS) and is poorly understood in infants. To address this lack of understanding and the need for an appropriate animal model in which to conduct relevant preclinical studies, we developed a model of infant sepsis-induced CRS in rat pups then evaluated the therapeutic potential of the phosphodiesterase (PDE) 4 inhibitor, rolipram. Rat pups at 17-18-days old were subjected to cecal ligation and puncture (CLP) to induce fecal polymicrobial sepsis. Uptake of Evans Blue dye was used to assess renal microvascular leakage. Intravital videomicroscopy was used to assess renal microvascular perfusion and oxidant generation. Glomerular filtration rate (GFR) was used to assess renal function. Left ventricular (LV) catheterization and echocardiography were used to assess cardiac function. Impairment of both cardiac and renal function developed rapidly following CLP, indicating type 5 CRS. Most notable were the rapid decline in LV diastolic function, the decline in cardiac output, renal microvascular failure, and the decline in GFR. A dose-response study with rolipram determined 0.1 mg/kg, ip as the lowest most efficacious dose to protect the renal microcirculation. Rolipram was then evaluated using a clinically relevant delayed dosing paradigm (a single dose at 6 hours post CLP). With delayed dosing, rolipram restored the renal microcirculation and reduced microvascular leakage but did not reduce oxidant generation in the kidney nor restore GFR. In contrast, delayed dosing with rolipram restored cardiac function. Rolipram also improved 4-day survival. In summary, CLP in the rat pup produces a clinically relevant pediatric model of sepsis-induced CRS. The PDE4 inhibitor rolipram was effective in improving renal microvascular function and cardiac function, which improved mortality. These findings suggest that rolipram should be evaluated further as adjunctive therapy for the septic infant with CRS.